SOSIALISASI DAN PENDAMPINGAN PELAPORAN KEWAJIABAN PERPAJAKAN UMKM DI DESA WALUYOJATI - Dewi Mariam Widiniarsih; Arum Arupi Kusnindar; Cindi Fatikasari (Tahta Media Grup, 2024)
Tax Obligation Assistance in Waluyojati Village, Ambarawa District to improve tax knowledge of Micro, Small and Medium Enterprises in Waluyojati Village, Ambarawa District better and have an impact on the level of taxpayer compliance. It is also expected that by increasing participants' understanding of the risks of tax audits, they will be able to reduce tax costs from tax fines for Macro, Small and Medium Enterprises. On the other hand, community service activities to assist the government in increasing tax revenues because more and more Micro, Small and Medium Enterprises are aware of their tax rights and obligations. The benefits of community service activities are focused on increasing the understanding of MSMEs, especially regarding how to calculate income tax payable, deposit income tax payable, and report income tax from their businesses. Also increase understanding of the risks of tax audits that may occur from every transaction in the MSME business, such as a good trading business. In this community service, a method with several stages is used, namely the observation, introduction, training and evaluation stages. The delivery of the material is presented with an overview of the basic material, the benefits of tax reporting for participants, and regarding the Matching of NIK and NPWP, at this stage the lack of knowledge about taxation among participants so that, after the socialization activity took place, public knowledge became higher and made it easier for the government to raise awareness of taxpayers. The discussion method, it was carried out with two-way communication and a question and answer session regarding the analysis of the material that had been delivered in the first stage and helped participants with the limited understanding of filling out the DJP online website which was assumed to be complicated for the community and provided an understanding of the validity for married women who are burdened independently because they live separately to continue to register for taxes. It is expected that the implementation of community service activities can increase participants' understanding of the risks of tax audits, they will be able to reduce tax costs from tax fines for Macro, Small and Medium Enterprises. On the other hand, community service activities to assist the government in increasing tax revenues because more and more Micro, Small and Medium Enterprises are aware of their tax rights and obligations